Improving Digital Literacy Skills for Youth Karang Taruna, Cigadung Village, Cibeunying Kaler District, Bandung City - Ine Mariane; Yuce Sariningsih; Riksa Alam Buanawaty; Hari Abdul Azis (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
Based on the results of the situation analysis, there are several problems with Youth Karang Taruna, Cigadung Village, Cibeunying Kaler District, Bandung City, namely: Low knowledge and understanding of digital literacy and low Digital Literacy Ability to become Smart Vlogers in order to become a productive generation. The purpose of this community service activity is to increase knowledge, understanding and ability about the Importance of Digital Literacy through Creativity Development to become a Smart Vloger as well as strengthening community social institutions in preventing online violence and cyber crime in people's lives, creating independence and a productive generation. The methods used are socialization and counseling, training, mentoring, and technical guidance. As a result of PKM activities, it is hoped that the Youth Karang Taruna, Cigadung Village, Cibeunying Kaler District, Bandung City will know, understand digital literacy, and be able to use internet digital media literacy skills safely in updating writing on the platforms they created to become Smart Vlogers to strengthen institutions. society in preventing online violence and cyber crime in people's lives, creating independence and a productive generation.